Norsk Ordbok ved ein krossveg. Rapport frå eit omstillingsprosjekt - Vikør, Lars S. (Nordiske Studier i Leksikografi, 2003)
On the fourth conference on Nordic lexicography (1997, see Vikør 1999), Norsk Ordbok (’Norwegian Dictionary’) was presented as an example of a dictionary project spanning several generations. In 2000, the Norwegian Ministry of Culture declared itself willing to strengthen the dictionary project in order to make completion possible already in 2014. This will necessitate a thorough reform process, which is now in the preparation phase. The paper gives a brief description of the latest developments and the current situation at the end of 2001, and discusses some problems and dilemmas which have to be solved in the process.